Avoidance tests as a tool to detect sublethal effects of oil‐impacted sediments. (30th April 2018) - Szczybelski, Ariadna S.; Kampen, Tineke; Vromans, Joris; Peeters, Edwin T.H.M.; van den Heuvel‐Greve, Martine J.; van den Brink, Nico W.; Koelmans, Albert A.
Abstract: Currently, risk assessment for oil contamination does not consider behavioral responses of benthos to oil toxicity. Avoidance of oil‐contaminated sediment by benthic amphipods, however, may be a highly sensitive endpoint for sublethal effects of commonly used distillate fuels. In the present study, the avoidance behavior of temperate freshwater ( Gammarus pulex ) and marine ( Gammarus locusta ) amphipods was tested by allowing them to choose between a reference sediment and a distillate marine grade A (DMA) oil‐spiked sediment. Avoidance of DMA‐spiked sediment at 1000 mg/kg dry weight was significant within the total exposure time (96 h) in G. pulex and within the first 72 h in G. locusta in 1 of 2 tests. Absence of DMA avoidance at lower concentrations (≤250 mg/kg dry wt) indicates that test species can only detect DMA above these concentrations. However, sensitivity to oil may vary according to the phenology and physiological conditions of the populations involved, such as the species temperature tolerance and reproductive stage. The results suggest that avoidance tests may be used as an alternative to traditional chronic toxicity tests provided that a causal link between avoidance and long‐term effects can be established. Environ Toxicol Chem 2018;37:1757–1766. © 2018 SETAC